LENDING NO LONGER UNDER THE CONTROL OF COPYRIGHT IN MALAYSIA - Khong, W. K. (Malaysian Journal of Library and Information Science, 1999)
Reports the amendment made by the Malaysian Copyright (Amendment) Act 1997 which came into force on 1 April 1999. Lending is no longer an exclusive right controlled by a copyright holder under the Malaysian Copyright Act 1987.